H/V measurements as an effective tool for the reliable detection of landslide slip surfaces: Case studies of Castagnola (La Spezia, Italy) and Roccalbegna (Grosseto, Italy). (April 2017) - Pazzi, Veronica; Tanteri, Luca; Bicocchi, Gabriele; D'Ambrosio, Michele; Caselli, Andrea; Fanti, Riccardo
Abstract: A variety of methods (detailed geomorphological surveys, geotechnical investigations, local instrumentation, satellite data, and radar interferometry) along with geophysical techniques may be used to investigate slope instabilities and to detect the inhomogeneities of materials as well as their properties, boundaries, and sliding surfaces. Of these techniques, the method based on seismic noise measurements allows abrupt changes in seismic impedance at landslide boundaries resulting from varying levels of seismic velocity and material density to be detected. Peaks of the Horizontal to Vertical Spectral Ratio have proven to serve as effective indicators of the resonance frequency of low-impedance surface layers. In this work, horizontal to vertical spectral ratio surveys of the Castagnola (La Spezia, Italy) and Roccalbegna (Grosseto, Italy) landslides were carried out. From roughly 100 single-station measurements made inside and outside the landslides at each site, we define a threshold number of single-station seismic noise measures beyond which information is redundant because the variation in reconstructed impedance contrast surfaces is not significant. This approach allows one to reliably retrieve the geometry of a landslide body, ultimately generating useful information for determining whether further measurements are needed to improve landslide body reconstruction. Highlights: H/V single-station measure to detect the deepest impedance contrast surfaces. IDW spatially interpolation in GIS environment to reconstruct depth maps. Depth maps as a reliable representation of the envelope of landslide slip surfaces. Optimization of the number of H/V measures taking into account landslide area.